Cohesive zone beam modelling of mixed-mode I-II delamination - Morais, A. B. de (2014)
Two cohesive zone beam models were developed for mixed-mode I-II delamination. The models were assessed by application to the moment-loaded double cantilever beam specimen, for which exact solutions are available. The main difficulties were caused by the very different distributions of the normal and shear tractions in the vicinity of the crack tip. This generated considerable local mode-mix variations along the cohesive zone. The separation controlled damage formulation was more sensitive to those difficulties, which could even compromise the accuracy of results. Instead, the energy controlled damage formulation proved to be robust and thus best suited for cohesive zone beam modelling of delamination.